Magnesium Isotopes in Pore Water of Active Methane Seeps of the South China Sea - Jin, Meng; Feng, Dong; Huang, Kangjun; Gong, Shanggui; Luo, Min; Peckmann, Jörn; Wang, Xudong; Hu, Yu; Chen, Duofu (Frontiers in Marine Science, 2022)
The magnesium (Mg) isotopic composition of marine authigenic carbonates is considered as promising archive of ancient seawater geochemistry and paleoenvironments. Previous experimental and theoretical work has shown that Mg isotope fractionation during carbonate mineral formation is a function of mineralogy and precipitation rate. However, information on Mg isotope fractionation is limited for well-defined precipitation rates in natural settings. Here, we investigate pore waters from sediments of an area of active methane seepage in the South China Sea. Low δ13C values (< −48.3‰ VPDB) of dissolved inorganic carbon (DIC) near the sulfate-methane transition zone (SMTZ) indicate that sulfate-driven anaerobic oxidation of methane (SD-AOM) is the predominant biogeochemical process. Pore water composition of dissolved Mg, calcium (Ca), and strontium (Sr) agrees with aragonite as the dominant carbonate mineral at the site ROV1, and high Mg-calcite at sites ROV2 and ROV4. Calculated carbonate precipitation rates are 0.92 μmol cm−2 yr−1 for site ROV2 and 1.24 μmol cm−2 yr−1 for site ROV4; these estimates are similar to previous calculations for seeps from other areas. The pore water δ26Mg values (−0.88‰ to −0.71‰) obtained for the three study sites are similar to those of seawater, in accord with a minor effect of Rayleigh fractionation due to abundant supply of Mg from seawater and insignificant consumption of Mg during carbonate precipitation. The modeled Mg isotope fractionation (ϵ = −2.0‰ to −1.0‰ for core ROV2; ϵ = −1.3‰ to −0.3‰ for core ROV4) can be explained by kinetic isotope fractionation during carbonate precipitation. The calculated carbonate precipitation rates and the degree of fractionation of Mg isotopes support the notion that fractionation is small at high precipitation rates. However, the carbonate precipitation rates calculated for the studied seep environments are much smaller than those in laboratory experiments, documenting a discrepancy of isotopic fractionation between carbonate authigenesis in laboratory experiments and natural environments. These results, including the modeled precipitation rates, provide new constraints for Mg isotope fractionation in natural settings.